Batangas City Public Library a study on their response to the social needs of its community - Lacsamana, Alistair Troy B.; Salang, Ma. Maura M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1995)
The basic elements of public library service include the communication of ideas, knowledge, information and experience; liaising with the cultural framework, responding to social needs: information, education and recreation. And among all libraries, it is the public library which must meet the challenge of poverty and deprivation. It is the requirement to respond to social needs that distinguishes from other types of library. According to David Liddle, the real business of libraries is community development, improving the quality of individual lives and encouraging the development of their communities. The key mission, therefore, is one of service and responsibility. Social responsibility is what all have towards the major public issues facing society (Martin, 1989).The study sought to answer the following questions:1. Is the Batangas City Public Library aware of the social needs of their communities? What are these?2. What is the level of understanding of the librarians on these social needs?3. How do the librarians respond to these needs?4. What are the barriers in meeting these needs?
The sample consists of one public library in Batangas. The respondents numbered 188 users and the librarians of each library. The descriptive survey method is used in this study. The questionnaire is the primary tool for data gathering supplemented by interviews
The findings of the study are the following: 1. that the Batangas City Public Library is only aware of one aspect of the social needs of their communities, its being an educational aid; 2. that librarians tend to believe that by performing their educational function they answer their community's social needs; also, since there is no existing study on their community's needs, they answer a need as it comes; 3. that the(y) respond mostly (to) the needs of students by providing them materials; 4. that the libraries, despite an improved image, indicate a common problem in insufficient funds for updated books and expansion of space, and qualified personnel.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Batangas City Public Library; Public Libraries -- Philippines -- Batangas